Aeromedical Evacuations Within the French Armed Forces: Analysis of 2, 129 Patients. Issue 3 (23rd October 2019) - Luft, Antoine; Corcostegui, Simon-Pierre; Millet, Marianne; Gillard, Jonathan; Boissier, Jerome; Rondy, Patrick; Bancarel, Jérôme; Carfantan, Cyril
Abstract: Introduction: The doctrine of medical support during French military operations is based on a triptych: forward medical stabilization, forward damage control surgery, and early strategic aeromedical evacuation (Strategic-AE). The aim of this study was to describe the last piece, the evacuation process of the French Strategic-AE. Methods: We conducted a retrospective cohort analysis using patient records from 2015 to 2017. All French service members requiring an air evacuation from a foreign country to a homeland medical facility were included. Data collected included age, medical diagnosis, priority categorization, boarding location, distance from Paris, type of plane and flight, medical team composition, timeline, and dispatch at arrival. Results: We analyzed 2, 129 patients evacuated from 71 countries, most from Africa (1, 256), the Middle East (382), and South America (175). Most patients (1, 958) were not severely injured, although some considered priority (103) or urgent (68). Diagnoses included disease (48.6%), nonbattle injuries (43%), battle stress (5.3%), and battle injuries (3%). 246 Strategic-AE used medical teams in flight, 136 of them in a dedicated Falcon aircraft. The main etiologies for those evacuations were battle injuries (24%), cardiovascular (15.4%), infections (8%), and neurologic (7.3%). The median time of management for urgent patients was about 16 hours but longer for priority patients (26 hours). Once in France, 1, 146 patients were admitted to a surgery department and 96 to an intensive care unit. Conclusion: This is the first study to analyze the French Strategic-AE system, which is doctrinally unique when compared to its North Atlantic Treaty Organization allies. North Atlantic Treaty Organization allies favor care in the theatre in place of the French early Strategic-AE. However, in the event of a high intensity conflict, a combination of these two doctrines could be useful.